Odpowiedzi

2009-09-27T18:59:05+02:00
A) (x+7)²= 49+14x+x²
d) (x - 6y)²= x²+ 36y² - 12xy
b) (4x - 1)²=16²+1-8x
e) (2x - 1/2y)²=2x²+¼y²-2xy
c) (1/2x + 3)²= ¼x²+3+3x
f) ( 0,6 +5y)²=0,36+25y²+6y
2009-09-27T19:05:48+02:00
A) (x+7) do potęgi 2 w kwadratowym nawiasie będę zapisywał potegi
(x+7)[2]=x[2] +2x*7 + 7[2] =x[2] + 14x +49
b) (4x - 1) do potęgi 2
(4x-1)[2]=(4x)[2]-2*4x + 1[2]=16x[2]-8x+1
c) (1/2x + 3)do potegi 2
(1/2x + 3)[2]=(0,5x)[2]+2*0,5x*3+3[2]=0,25x[2]+3x+9
d) (x - 6y) do potęgi 2
(x - 6y)[2]=x[2]-2*x*6y +(6y)[2]=x[2]-12xy+36y[2]
e) (2x - 1/2y)do potegi 2
(2x - 1/2y)[2]=(2x)[2]-2*2x*0,5y+(0,5y)[2]= 4x[2]-2xy+0,25*y[2]
f) ( 0,6 +5y)do potegi 2
( 0,6 +5y)[2]=0,6[2]+2*0,6*5y+(5y)[2]=0,36+6y+25y[2]